Philosophical inquiry method for enhancing higher order thinking in teaching aqidah to form two students - Wan Yusoff, Wan Mazwati; Hamzah, Lina Mursyidah (Akademi Pengajian Islam, Universiti Malaya, 2016)
The present Muslims are facing challenges posed by ideologies such as secularism, liberalism, materialism. Muslims who have haphazard worldview and weak in thinking can easily be influenced by these ideologies. Therefore, forming Islamic worldview through Teaching Islamic education, especially aqidah is challenging. The popular method of teaching is lecturing which most of the time fail to attract students’ attention, what is more to provoke higher order thinking. Teacher requires students to write notes and memorize contents of text book which involved lower order thinking. This led to superficial understanding of aqidah which is vital for development of Islamic worldview. Aqidah is a strong unwavering conviction without any doubt in one’s heart based on logical, historical, and empirical evidences of reported truth on Oneness of God which become the foundation of Islamic thought and actions. True understanding of aqidah provides proof of Islamic belief and serves as filter of pseudo religion and false worldview which leads to right actions or good moral character epitomized by personality characteristics of Prophet Muhammad. Therefore, teaching for deep understanding of aqidah is vital and the highest priority. Philosophical inquiry method has been proven effective in eliciting deep and excellent thinking in fundamental issues such as metaphysics, epistemology and ethics. These fundamental issues are the subject matters of aqidah. Therefore, this research project attempted to evaluate the effectiveness of philosophical inquiry method in stimulating students to ask higher order thinking questions. This study employs qualitative research method to collect and analyze data. Form two students were taught aqidah using philosophical inquiry method for 60 minutes per week for six weeks. The data revealed that philosophical inquiry method had succeeded in provoking students to ask higher order thinking questions and assisting students in reasoning and justifying their beliefs.